Pengaruh Total Asset Turnover, Earning Per Share dan Debt to Asset Ratio Terhadap Harga Saham Perusahaan (Studi Kasus pada Perusahaan Sektor Healthcare yang Terdaftar di Bursa Efek Indonesia periode 2019-2023) - Risvila, Lia; Mulyandini, Vita Citra (Portofolio: Jurnal Ekonomi, Bisnis, Manajemen, dan Akuntansi, 2025)
This research aims to examine the effect of financial ratios—Total Asset Turnover (TATO), Earnings per Share (EPS), and Debt to Asset Ratio (DAR)—on stock prices of companies in the healthcare sector listed on the Indonesia Stock Exchange (BEI) between 2019 and 2023. The healthcare sector, which has seen notable stock price fluctuations, especially during and after the COVID-19 pandemic, is the focus of this study. A quantitative approach using multiple regression analysis is employed to assess how these financial ratios influence stock prices. The sample includes 16 healthcare companies selected through purposive sampling, with data derived from their annual reports. The findings reveal that while TATO and DAR do not have a significant impact on stock prices, EPS plays a significant role in influencing stock prices. Additionally, a combined analysis of all three variables (TATO, EPS, and DAR) shows that they collectively have a significant effect on stock prices in the healthcare sector. These results offer valuable insights into the factors driving stock price changes and underscore the importance of EPS as a crucial indicator for investors in the healthcare industry.